The "Human Emotions" and the new "Perrotta Human Emotions Model" (PHEM-2): Structural and functional updates to the first model - Giulio Perrotta; Vanessa Basiletti; Stefano Eleuteri (Open Journal of Trauma - Peertechz Publications, 2023)
Background: The first version of the Perrotta Human Emotions Model (PHEM) responded to the need for better structuring, in a functional framework, of emotions and sentiments, giving the proper role to anxiety, according to a neurobiological perspective, in a strategic scheme, but needs structural and functional corrections.  Methods: Clinical interview, based on narrative-anamnestic and documentary evidence, and battery of psychometric tests.  Results: Statistical comparison of data obtained by administering PHEM-1 versus data obtained by administering PHEM-2 reported an R = 0.999, with p = ≤0.001, as is the case when testing clinical utility by assessing it using MMPI-2-RF and PICI-2.  Conclusion: This research confirms the clinical usefulness of administering the PHEM-2, compared with the previous version, during psychotherapeutic encounters conducted according to the brief or otherwise integrated strategic approach.